Effects of Bin Location on Waste Sorting Behavior in Junior High Schools: A Field Experiment - Olapegba, Peter Olamakinde; Uye, Emmanuel Etim (Mitra Edukasi dan Publikasi, 2025)
Solid waste management remains a pressing challenge that affects environmental quality and public well-being. This study examined the influence of bin location on waste sorting behavior among students in selected secondary schools in Lagos State, Nigeria. This study employed a 2 × 4 quasi-experimental design, in which bins for recyclable materials were placed in classrooms and corridors for a 10-day period. Recyclable waste collected was counted, weighed, and analyzed using descriptive and inferential statistics. The results showed that bin location marginally improved sorting behavior, with more materials deposited in classroom bins than in corridor bins. This finding suggests that bins placed in classrooms provide greater accessibility and convenience, thereby encouraging consistent sorting behavior, while bins in corridors are less effective due to distractions and increased foot traffic. The study concludes that strategic placement of bins can enhance students’ participation in waste sorting and contribute to more sustainable waste management practices. School authorities are therefore encouraged to consider bin placement as a behavioral intervention to foster environmentally responsible habits among students.